The Effect of Profitability and Net Working Capital on Cash Holding Moderated by Firm Size - Siti Rahayu; Dyah Ratnawati (Al-Buhuts, 2024)
This study aims to test and prove empirically whether profitability and net working capital partially affect cash holding and whether firm size as a moderating variable is able to moderate the relationship between profitability and net working capital on cash holding. This research utilizes secondary data sourced of financial reports consumer non-cyclical sector companies that are listed on the Indonesia Stock Exchange from 2020 to 2022. Sampling is conducted through purposive sampling, where samples are chosen according on the predetermined criteria. According to the predetermined criteria, 50 companies were selected with 3 years of observation are obtained, resulting in a total of 150 samples for this study. In this research, the analytical methods employed are multiple linear regression and Moderated Regression Analysis (MRA) using SPSS version 29 as the statistical tool. The results of this study indicate that partially, profitability and net working capital affects cash holding. Additionally, the interaction test results indicate that firm size strengthens the relationship between profitability and cash holding, as well as the relationship between net working capital and cash holding.